2003
DOI: 10.1163/156854103322746922
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid-induced suppression of Meloidogyne incognita infestation of okra and cowpea

Abstract: Salicylic acid (SA) applied as 10 mM foliar spray to okra (Abelmoschus esculentus) cv. Purbani Kranti and cowpea (Vigna unguiculata) cv. Pusa Ruby plants 24 h before inoculation of roots with Meloidogyne incognita juveniles, reduced infestation. Salicylic acid had no direct influence on plant growth and did not kill nematodes in an in vitro test. It induced increased accumulation of a 14 kDa pathogenesis-related protein (PR-1) in roots of both non-inoculated and inoculated salicylic acid-sprayed okra but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 0 publications
5
52
0
Order By: Relevance
“…These results are in agreement with results of Mostafanezhad et al (2014), who also found that soil drench and spraying tomatoes with SA significantly reduced the diameter of M. javanica galls and numbers of galls and egg masses; treatments also increased the activity of enzymes and phenolic compounds. Mukherjee et al (2012) showed that the num- Nandi et al (2003), who when spraying SA onto leaves of cowpea and okra plants inoculated with eggs of M. incognita significantly reduced the numbers of galls and nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with results of Mostafanezhad et al (2014), who also found that soil drench and spraying tomatoes with SA significantly reduced the diameter of M. javanica galls and numbers of galls and egg masses; treatments also increased the activity of enzymes and phenolic compounds. Mukherjee et al (2012) showed that the num- Nandi et al (2003), who when spraying SA onto leaves of cowpea and okra plants inoculated with eggs of M. incognita significantly reduced the numbers of galls and nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential use of elicitors to induce resistance against various RKN species is being widely investigated (Oka et al, 1999;Nandi et al, 2003;Chinnasri et al, 2006;Viera dos Santos et al, 2013). In this study, we investigated the Overall, based on our pot plant experiments, the efficacy of the tested elicitors can thus be ranked, from most effective to least, as follows; BABA, Bion and Harpin.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two BABA concentrations evaluated, we found that the most effective treatment overall was 20mM BABA. It is interesting to note that several studies have noted that 20 mM (not less or more) is the most effective concentration of BABA to induce resistance against a wide variety of pathogens including Penicillium digitatum, Phytophthora infestans and root knot nematode (Porat et al, 2003;Oka et al, 1999Cohen et al, 2001 (Nandi et al, 2003;Chinnasri et al, 2006;Vieira dos Santos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations